L' hagiographie : un «genre» chrétien ou antique tardif? - Uytfanghe, Marc Van (Analecta Bollandiana, 1993)
The present study, an updated French version of the final lecture delivered at the 1986 Nimegue-congress on the cult of the saints in the first centuries of the Christian era, is a re-examination of the old problem of the originality of the Christian hagiography. It introduces an answer which is no longer based on the concept of literary genres but on the concept of "hagiographical discourse". This "hagiographical discourse" was a common feature of the culture of the (later) Roman Empire but a specifically Christian "hagiograhical discourse" appears to have established itself within this general discourse.